2016
DOI: 10.14474/ptrs.2016.5.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different surface plank exercises on core muscle activity

Abstract: Objective: This study compared the muscle activities of the erector spinae (ES), the external oblique (EO), and the rectus abdominis (RA) on three different surfaces. The purpose of this study was to determine which surface induces the highest muscle activity during the plank exercises. The information from this study can be used to recommend plank exercises to athletes and patients with weak core muscles. Design: Cross-sectional study. Methods: The subjects include 20 adult males attending S University in Seo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…5 In recent years, various studies have been reported on posture to maximize the effects of plank exercise performance. 6 Many studies on effective exercise methods have been reported on not only the general plank position, but also on the use of a sling, Swiss ball, Togu, etc using an unstable support surface, 7,8 as well as arm angles and changes in various lower extremity conditions etc. 9,10 Slings exercises are composed of multifaceted exercises performed in multiple planes and joints through the use of the effects of gravity placed on the body weight, and are difficult to adapt to and maintain balance due to changes in inclination.…”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, various studies have been reported on posture to maximize the effects of plank exercise performance. 6 Many studies on effective exercise methods have been reported on not only the general plank position, but also on the use of a sling, Swiss ball, Togu, etc using an unstable support surface, 7,8 as well as arm angles and changes in various lower extremity conditions etc. 9,10 Slings exercises are composed of multifaceted exercises performed in multiple planes and joints through the use of the effects of gravity placed on the body weight, and are difficult to adapt to and maintain balance due to changes in inclination.…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases where exercise planning to improve the overall strength and muscular endurance, the activation level of the muscles with the primary lifting role in performed exercises could determine the exercise preference. Plank and bridge exercises increase the overall body strength, and could also be used for therapeutic purposes (6,10). In addition, these exercises are frequently preferred in clinical applications because they contain isometric contractions that are suitable for problems such as painful range of motion or muscle weakness (28).…”
Section: Discussionmentioning
confidence: 99%
“…Plank and bridge exercises are some of the most commonly used calisthenic exercises in terms of both the development of the strength and their therapeutic benefits. Plank and bridge exercises are posture exercises designed to use bodyweight to resist gravity (6). They are known to be beneficial in improving muscular endurance and gaining essential strength (7).…”
Section: Introductionmentioning
confidence: 99%
“…The maximal voluntary isometric contraction (MVIC) was measured to standardize the action potential of each muscle. To encourage maximal activation of the rectus abdominis, subjects were instructed to perform trunk flexion from the supine position, bend and rotate the trunk to the opposite side for the external oblique, and lateral trunk rotation for the internal oblique muscle [15]. The evaluator provided resistance toward the opposite direction of each muscle position to the induce maximal isometric contraction of each muscle [16].…”
Section: Outcome Measuresmentioning
confidence: 99%